Chapter 8: Ethics and Criminal Law Practice - Tanovich, David M. (2017)
This chapter explores the more general and arguably distinct ethical obligations of those who practice criminal law either as defence lawyers or prosecutors. As you read this chapter, you should ask yourself whether you are satisfied with the justifications offered for the ethical rules that we have carved out for defence lawyers and prosecutors in this context and whether you think we have achieved the right balance. To assist you in thinking about the modern-day ethical roles of criminal lawyers, we begin with two historical cases, one from England and the other from Quebec, which frame the obligations in arguably extreme terms – defence lawyers justified in unbridled zealousness within the bounds of the law on the one hand, and the prosecutor as a “minister of justice” on the other. In reading the descriptions of the cases consider whether you think the duties of defence lawyers and prosecutors should be so different. What would justify that sort of difference? What common framing for the duties of defence lawyers and prosecutors might be available?
Keywords: David Tanovich